Improving Children's Language Aspects Through Educational Game Tool Mystery Sock at Kindergarten - Wahyu Cahyaninghati; I Made Gede Anadhi; Ida Bagus Komang Sindu Putra (TEMATIK: Jurnal Pemikiran dan Penelitian Pendidikan Anak Usia Dini, 2023)
Language is a way to communicate between individuals and other individuals. In Taman Kurnia Kindergarten Denpasar, there are some children in learning who are less active in delivering questions and answers in play activities and questions and answers from teachers.  The purpose of this study was to improve language development in children with APE Mystery Sock.  The method used is descriptive qualitative, data collection techniques through observation, interviews and documentation. The source of the data is teachers, children aged 5-6 years in Taman Kurnia Kindergarten based on purposive sampling techniques. The results showed that based on the findings obtained by the researchers, the first data on the cognitive abilities of students during the first cycle of learning were 4 children in the category of developing as expected, and increasing by 18 children to 22 children in cycle II in the category of developing very well and developing as expected. Based on this presentation, it can be seen that the mystery sock game can help the language development of students in Taman Kurnia Denpasar.